Studies in asymmetric synthesis - Learmonth, Robin Alec (Rhodes University, Faculty of Science, Department of Chemistry, 1991)
The concept of combining two well established areas of organic chemistry, viz., organosilicon chemistry and the use of chiral auxiliaries, into a viable, alternative method of asymmetric synthesis has only very recently begun to receive attention. At the outset of this investigation, no asymmetric reactions of silyl enol ethers, chiral by virtue of optically active substituents on the silicon, had been reported. A range of novel chiral silyl enol ethers have thus been prepared from a variety of ketones, including pinacolone, cyclohexanone, and Î±-tetralone, and employing menthol, borneol, and cholesterol as chiral auxiliaries. These preparations have been achieved via several distinct routes, including a novel convergent approach involving the isolation of either the chloro(menthyloxy)dimethylsilane or the (bornyloxy)chlorodimethylsilane. The MS and NMR spectra of these silyl enol ethers were examined in detail and, in the case of the crystalline cholesteryloxy silyl enol ether, the X-ray structure has been determined. The potential of chloroalkoxysilanes to act as general, chiral derivatizing agents has been established by the preparation of diastereomeric silyl acetal mixtures of racemic secondary alcohols (e.g. I-phenylethanol and 2-octanol). The experimental diastereomeric ratios, obtained by GLC and Â¹H NMR spectroscopy, approached the expected value of unity, confirming the potential of the alkoxychlorosilanes as chiral probes. The chiral silyl enol ethers have been successfully oxidized to the corresponding Î±-siloxy ketones employing MCPBA, MMPP, and 2-(phenylsulphonyl)-3-phenyloxaziridine as oxidizing agents and the diastereomeric excesses obtained, which varied from 0 to 16%, indicated some potential for stereochemical control. Alkylation and hydroxyalkylation reactions of the silyl enol ethers have yielded the expected Î±-iert-butyl and Î²-hydroxy ketones in good to excellent material yields, with the enantiomeric excesses, as determined by chiral shift reagent studies, reaching 14%. To improve the stereo control in these reactions, attempts have been made to prepare chiral silyl enol ethers with auxiliaries possessing the potential for transition state complex co-ordination in the reactions under consideration. The preparation of such silyl enol ethers, incorporating the proline-derived auxiliaries, N-methyl-2-hydroxymethylpyrrolidine and 2-methoxymethylpyrrolidine met with only limited success. In an alternative approach, three derivatives of 2,3-dihydroxybornane have been prepared. However, two of these auxiliaries, viz., 3-exo-benzyloxy-2-exo-hydroxybornane and 3-exo-(1-methoxyethoxy)-2-exo-hydroxybornane failed to form silyl enol ethers, even under considerably more vigorous conditions than normally employed. The third derivative, 3,3-ethylenedioxy-2-hydroxybornane has been successfully utilized in the preparation of a pinacolone-derived chiral silyl enol ether. Hydroxyalkylation of this compound with benzaldehyde has yielded the Î²-hydroxyketone with significantly improved enantiomeric excess (26%) and a transition state complex has been proposed to rationalize this improvement.
Keywords: Organic compounds -- Synthesis; Stereochemistry; Organosilicon compounds; Chirality; Chemical tests and reagents